DIVERSITY OF SOIL ARTHROPOD IN GREEN BARRIER AREA PT. PUSRI - Hidayat, Arif; Zulkifli, Hilda; Irsan, Chandra (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
The research was conducted to inventory and identify as well as acknowledge the correlation between vegetation type with soil arthropods in the Green Barrier area of PT Pusri. PT. Pusri green Barrier area is 28 hectares and dominated by 10 types of vegetation, such as, the Angsana (Pterocarpus indicus Wild), Bambu (Bambusa Sp), Beringin (Ficus benyamina), Buah Roda (Hura crepitans L), Jati (Tectona grandis L), Kelampayan (Neolamarckia cadamba) , Ketapang (Terminalia catappa L), Mahony (Swietenia macrophylla King), Pulai (Alstonia scholaris), and Sengon (Paraserianthes falcataria L). Soil arthropods were collected by using pit fall traps and funnel barlese-tullgren in every type of vegetation, between July-August 2015. Identification of arthropod genera Identification has been done in Entomology Laboratory of the Agriculture Plant Disease Faculty Sriwijaya University, and analysis of soil organic in the Laboratory of Soil Faculty of Agriculture Sriwijaya University. The results were obtained into 3 classes of soil arthropods belonging to the 10 orders, 28 families and 35 genera. The diversity index value of soil arthropods in various types of vegetation is classified moderately (H= 1-3), and no type of soil arthropods were dominant, mean that soil arthropods with different types spread over in the various types of vegetation in the area of Green Barrier PT. Pusri. Light intensity abiotic factors play an important role in the life of the soil arthropod communities in vegetation Sengon (Paraserianthes falcataria L) with a correlation coefficient 1.00Keywords: soil arthropods, community structure, a biotic factors, Green Barrier PT. Pusri